Beyond artificial tears: a new era in dry eye disease management – a review article - Sapikowski, Jakub Mikołaj; Juchniewicz, Agata; Janiszewska, Maria; Kuba, Iga; Jagodzińska, Julita; Góralczyk, Mikołaj; Grześkowiak, Martyna; Idziński, Jakub; Lubomska, Anna; Jętasiewicz, Igor (Journal of Education, Health and Sport, 2026)
Dry eye disease (DED) is a prevalent and increasingly recognized disorder of the ocular surface that poses a significant clinical and public health challenge worldwide. Its complex and heterogeneous nature reflects the interplay of tear film instability, inflammation, epithelial dysfunction, and neurosensory abnormalities. The evolving understanding of DED pathophysiology has led to substantial changes in diagnostic criteria and therapeutic paradigms, shifting from purely symptomatic management toward mechanism-based and individualized approaches. Ongoing advances in molecular biology, immunology, and biomedical technology continue to reshape the therapeutic landscape of DED. In light of the growing clinical burden and the evolving understanding of DED as a complex, multifactorial disorder of the ocular surface characterized by loss of tear film homeostasis, hyperosmolarity, inflammation, and neurosensory abnormalities—as defined by the Tear Film & Ocular Surface Society in the TFOS DEWS III report—the purpose of this study was to comprehensively review the current evidence regarding DED pathophysiology, risk factors, classification, diagnostic algorithms, and contemporary therapeutic strategies, with particular emphasis on mechanism-based and emerging treatments.